'Mucho malo for fascisti': Languages and Transnational Soldiers in the Spanish Civil War. (3rd April 2019) - Marco, Jorge; Thomas, Maria
Abstract : This article explores the linguistic experiences of transnational soldiers, using the Spanish Civil War as a case study. It argues that communication difficulties provoked by linguistic diversity within the Republican war effort and particularly within the International Brigades, caused the high command to move from a utopian, internationalist policy to a more pragmatic approach. The article evaluates the role played by language intermediaries in this evolving policy and in the wider Republican war effort. Finally, it argues that soldiers grassroots experiences of language contact forged new linguistic forms which underlined a strong sense of shared purpose and identity.